Increases in groundwater arsenic concentrations and risk under decadal groundwater withdrawal in the lower reaches of the Yellow River basin, Henan Province, China. (1st March 2022) - Cao, Wengeng; Gao, Zhipeng; Guo, Huaming; Pan, Deng; Qiao, Wen; Wang, Shuai; Ren, Yu; Li, Zeyan
Abstract: The spatiotemporal variability in groundwater arsenic concentrations following extensive groundwater extractions over decades was rarely studied on a large scale. To fill this gap, variations in groundwater arsenic concentrations in the North Henan Plain in China from 2010 to 2020 were investigated. The possibility of high-arsenic groundwater (>10 μg/L) was higher than 40% in aquifers within a distance of 100 m from paleochannels. This may be due to the fact that deposits in paleochannels were rich in organic matter and suitable for arsenic enrichment. Following groundwater withdrawal over ten years from 2010 to 2020, nearly half of groundwater samples (44%) were elevated in groundwater arsenic concentrations, and the proportion of high arsenic groundwater increased from 24% in 2010 to 26% in 2020. These may be related to enhanced Fe(III) oxide reduction under decadal groundwater withdrawal. However, around 56% groundwater samples were decreases in arsenic concentrations because of increased NO3 − levels in these samples in 2020. Furthermore, extensive groundwater withdrawal decreased groundwater tables averagely by 4.6 m from 2010 to 2020, which induced the intrusion of high-arsenic groundwater from shallow aquifers into deeper ones. More importantly, the long-term groundwater pumping has perturbed groundwater flow dynamics and redistributed high-arsenic groundwater in the plain, leading to 18% more areas and 33.8% more residents being potentially at risk. This study suggests that the threat of groundwater overexploitation may be much more severe than previously expected. Graphical abstract: Image 1 Highlights: Proportions of high arsenic groundwater increased with proximity to paleochannels. Redox sensitive components changed temporally evidently but major ions varied less. Decreasing arsenic trends occurred in 56% samples due in part to elevated NO3 − level. Elevated arsenic occurred in 44% samples due to enhanced Fe(III) oxide reduction. Redistribution of high arsenic groundwater by exploitation increased arsenic risk.